2014
DOI: 10.1186/1471-2407-14-491
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose and survival of patients with stage IV non-small cell lung cancer undergoing concurrent chemotherapy and thoracic three-dimensional radiotherapy: reanalysis of the findings of a single-center prospective study

Abstract: BackgroundThe objective of this study was to evaluate the radiation dose and response in terms of local-regional progression-free survival (LRPFS) and overall survival (OS) of patients with stage IV non-small cell lung cancer (NSCLC) undergoing concurrent chemotherapy and thoracic three-dimensional radiotherapy.MethodsIn all, we enrolled 201 patients with stage IV NSCLC in this study and analyzed OS in 159 patients and LRPFS in 120.ResultsThe 1-, 2-, 3-, and 5-year OS rates were 46.2%, 19.5%, 11.7%, and 5.8%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Su et al suggested that concurrent chemotherapy with aggressive thoracic radiotherapy (TRT) was shown to play an important role in improving OS for stage IV NSCLC [20]. Ouyang et al pointed out that treatment of IV NSCLC undergoing concurrent chemotherapy and RT might prolong survival in a single-center prospective study [21]. These two investigations are supporting our results in some extent for stage IV survival of two therapies.…”
Section: Discussionsupporting
confidence: 82%
“…Su et al suggested that concurrent chemotherapy with aggressive thoracic radiotherapy (TRT) was shown to play an important role in improving OS for stage IV NSCLC [20]. Ouyang et al pointed out that treatment of IV NSCLC undergoing concurrent chemotherapy and RT might prolong survival in a single-center prospective study [21]. These two investigations are supporting our results in some extent for stage IV survival of two therapies.…”
Section: Discussionsupporting
confidence: 82%
“…Studies with small sample sizes have shown that local treatments including surgery could prolong survival in metastatic EC10111213. Studies have shown that surgery and/or radiotherapy can improve survival in patients with stage IV malignant tumors1415. In this study, we analyzed the metastatic EC using a population-based national registry (Surveillance Epidemiology and End Results, SEER) to determine the impact of local treatment strategies on survival in metastatic EC.…”
mentioning
confidence: 99%
“…Acute radiation pneumonitis and chronic radiation fibrosis represent common consequences of radiation exposure in the setting of treatment of various cancers (22), including non-small cell lung cancer, small cell lung cancer (23), breast cancer (24), esophageal cancer (25), mediastinal tumors (26), and head and neck tumors (27). Although the underlying biology of radiation-induced injury to the lung is becoming increasingly known, few actionable targets exist for the purposes of therapy.…”
Section: Discussionmentioning
confidence: 99%